The Impact of YouTube Culinary Product Review Videos Towards Viewers Purchase Intention In Indonesia (Journal of Business and Management, 2022)
The culinary industry is the largest sub-sector in Indonesia, contributing to GDP from the creative economy with an average of 43% per year of the total GDP of the creative economy. Due to the growth of the culinary industry in Indonesia, culinary business owners often face several issues. One of them is how to maximize their marketing strategy through a social media platform. Culinary product marketing is now affected by the younger consumer's lifestyle and preference. They use social media such as YouTube to seek product information. Many YouTube influencers specifically created review videos of a culinary product called Food Vloggers. This channel is believed to lead to consumer purchase intention. This research aims to identify the factors that influence viewers purchase intention of a culinary product after watching the review video on YouTube and give recommendations that influencers can implement to create good content for a culinary product review. The data was collected through an online questionnaire and analyzed by PLS-SEM to assess the relationship between the factors. The result shows the number of views, likes, comments, and replies, perceived usefulness, attractiveness, trustworthiness, and attitude towards the product are significantly affecting viewers purchase intention of the culinary product. Hopefully, the results of this research can give benefits to readers, influencers, and culinary business owners to develop their marketing strategy in the culinary industry.Keywords: Culinary product, food vloggers, influencers, PLS-SEM, purchase intention, review video, YouTube